Karl Schmidt-Rottluff Stipendium 9. - Harten, Jürgen; Kohrs, Klaus Heinrich; Kunsthalle, Düsseldorf (Düsseldorf : Kunsthalle Düsseldorf, 1995)
Striebel, Bernard C. ; Virnich, Winfried ; Doberauer, Anke ; Grosse, Katharina ; Hörnschemeyer, Franka ; Rosenthal, Frank ; Kottmann, Norbert ; Richter, Christiane ; Ruhland, Eva ; Doberauer, Anke
Doos met 9 catalogi, cataloog per kunstenaar
biografie
Duits
Karl Schmidt-Rottluff Stipendium 9, Kunsthalle Düsseldorf, 15. Dezember 1995 bis 14. Januar 1996
boek